Multimode nonlinear fiber optics, a spatiotemporal avenue - Krupa, Katarzyna; Tonello, Alessandro; Barthélémy, Alain; Mansuryan, Tigran; Couderc, Vincent; Millot, Guy; Grelu, Philippe; Modotto, Daniele; Babin, Sergey A.; Wabnitz, Stefan (APL photonics, 2019)
We provide a perspective overview of the emerging field of nonlinear optics in multimode optical fibers. These fibers enable new methods for the ultrafast light-activated control of temporal, spatial, and spectral degrees of freedom of intense, pulsed beams of light, for a range of different technological applications.